Research of young female handball players` self-actualizing mental states - Popovych, I.; Halian, I.; Lialiuk, G.; Chopyk, R.; Karpenko, Y.; Melnyk, Y. (Journal of Physical Education and Sport, 2022)
The purpose is to establish the interdependence of self-actualization characteristics and to develop the factor structure of self-actualization mental states in young female handball players. Methods. Valid psychodiagnostic methods that have been validated in a number of sports studies were employed; targeted surveillance using standard protocol forms; factor analysis of lowering the proportionality of self-actualization elements using the ANOVA method; and Spearman correlation (rs). Results. The study`s methodological basis was the view of personality as an open, dynamic, self-organizing, and self-developing system. The psychological patterns of youth sports achievements are described. The parameters for young female handball players` self-actualization have been established. The self-actualizing mental states factor structure is built. F1 "Search for Self-Actualization" (25.943%), F2 "Self-Motivation" (21.948%), F3 "Temporal Incongruence" (14.737%), F4 "World Perception" (9.221%) and F5 "Attitude to Cognition" (4.453%) were identified as the five factors (76.312%). F1 and F2 were discovered to be the most consistently loaded with self-regulatory components. F1 and F2 have the strongest correlation (p=.05; p=.01). F3 "Temporal Incongruence" was identified as the most harmful dominating self-actualizing mental state. Total concentration on the future and the objective narrows the attention of young female handball players to the outcome while disregarding the quality of the process, which has a detrimental impact on overall performance. Conclusions. It is experimentally defined and proved that the study`s findings should be implemented in the training and rehabilitation of young female handball players. Self-actualizing mental states that have been established and defined are a hidden resource of good sports performances in female handball players. The coaching staff`s discovery of the prevalent self-actualizing mental states of female handball players provides a tactical advantage over the opponent. It should be emphasized that the combination of procedural component and outcome reveals the athlete`s psychological development and leads to the attainment of consistently excellent performance.